LA ETNOGRAFÍA: EL DESCUBRIMIENTO DE MUCHOS MÉXICOS PROFUNDOS. ENTREVISTA A ANDRÉS FÁBREGAS PUIG. - Olivos Santoyo, Nicolás; Cuadriello Olivos, Hadlyyn (Andamios)
The article presents an interview with Mexican anthropologist Andrés Fábregas Puig. Fábregas Puig discusses the changing field of anthropology and ethnography during the time since his training and education, the impact of ethnography and anthropology on his generation in Mexico, and the development of new techniques and theoretical frameworks for the study of ethnography.